Evaluating Changes in the Sensory Profiles of Smoked Fish Across Different Processors During Storage - Kristina Haryati (Jurnal Biologi Tropis, 2026)
Smoked fish remains a widely consumed product due to the characteristic taste and aroma acquired during the smoking process. Smoked fish is still produced traditionally using coconut shells and mangrove wood. The use of shells and mangrove wood is done because both are classified as hardwood, so they can affect the organoleptic qualities of smoked fish. This study sought to evaluate the organoleptic profiles of smoked fish sourced from different producers, specifically comparing the effects of coconut shell and mangrove wood combustion. This method is divided into 2 stages: the raw material preparation stage and the fish smoking stage. The fish sample used was fresh tuna smoked using coconut shell and mangrove wood fuel. Organoleptic testing carried out included appearance, odor, and texture using a scoresheet. The results showed that for all smoked fish samples using coconut shells and mangrove wood against the storage period, the quality value for day 0 was 9 (Very Liked), then the value decreased on the 2nd day of storage, with a quality of Very Dislike to Dislike. In conclusion, the organoleptic specification value decreased during storage, depending on the type of fuel. The use of fuel did not affect storage time, as a decrease in quality was observed on the second day, indicated by the appearance of mold on the samples. It is recommended that microbiological testing of the smoked fish be conducted.